Penerapan Model Pembelajaran SPICS (Student Centered, Problem Based, Interest, Confident and Satisfaction) Untuk Meningkatkan Hasil Belajar IPA Terpadu Siswa Kelas VII MTs Negeri Pamenang Tahun Ajaran 2018/2019 - Hadi Nur Arifin; Apriza Hongko Putra; Eni Yulianti (BIOCOLONY, 2018)
This research was motivated by the learning outcomes of students in MTS Negeri Pamenang Integrated Science learning, most of them are still under the classical KKM set by the school, this shows that the Integrated Science learning process has not run optimally. This study aimed to improve Integrated Science learning outcomes for grade VII MTS N Pamenang students with the application of SPICS (Student Centered, Problem Based, Interest and Confident and Satisfaction) learning models, in class VII MTS N Pamenang in the 2018/2019 school year. Thie type of research was classroom action research, where the subjects in this study were students of class VII MTS N Pamenang consisted of to 28 people, while the object in this study was SPICS Learning Model (Student Centered, Problem Based , Interest, Confident and Satisfaction). The procedure in this study consisted of the stages of planning, implementing actions, observation and evaluation and reflection. Data collection form of student and teacher activity observation sheets and evaluation test used. Students have received grades according to the KKM, meaning that action research in the second cycle has achieved a minimum target of 75% achievement of students achieving KKM. Based on the research results obtained in the first cycle the average test score of 73.03 cycle with a percentage of completeness 64% or 19 students who graduated according to the defined KKM that is 75 in the second cycle found that student learning outcomes increased to 77.57. Based on the data analysis, the research can be concluded that by using SPICS (Student Centered, Problem Based, Interest, Confident and Satisfaction) learning models, it can improve the learning outcomes of class VII MTS N Pamenang in the 2018/2019 school year.